Hazard identification, risk assessment and risk control: a study at precision part manufacturing industry - Misran, Amirul Faiz; Yahya, Muhammad Alief Ikhram; Mahmood, Salwa; Khalid, Amir; Jaat, Norrizam; Razali, Azahari; Noranai, Zamri (Penerbit UTHM, 2020)
Occupational Safety and Health Act 1994 is a piece of Malaysian legislation which use to discipline many types of specialized fields. In other words, Occupational Safety and Health Act 1994 covers in many aspects for examples the social, mental, and physical. The objective of this study is to spur the adaptation of safety and health environment at the Top Speed Precision Engineering (M) Sdn. Bhd. based on the existing potential hazard. There are some possible injury cases happen due to the accident in the workplaces. This might cause by lack of awareness among workers regarding on safety and health during working. It is very important for workers or employers to emphasize safety and health at the workplace and lack of management control also can often leads to accidents. The data collection was carried out through site visit, observation, interview session and analysis by using the HIRARC method. This study suggested several precautions that can be made regarding on safety and health after identify the hazard at the workplace.